Traditional African Dishes Prepared From Local Biofortified Varieties of Pearl Millet: Acceptability and Potential Contribution to Iron and Zinc Intakes of Burkinabe Young Children - Hama-Ba, Fatoumata; Mouquet-Rivier, Claire; Diawara, Bréhima; Weltzien, Eva; Icard-Vernière, Christèle (Frontiers in Nutrition, 2019)
Biofortification is among the food-based strategies, recently implemented and still in development, to fight micronutrient deficiencies. Three cereal-based traditional dishes of Sub-Saharan Africa (tô paste, pancakes and gruel) prepared from one local (Gampela), or two biofortified (GB 8735 and Tabi) varieties of millet were assessed for their (i) acceptability by local consumers, (ii) iron and zinc absorption predicted by phytate-to-mineral molar ratios and (iii) contribution to the iron and zinc requirements of young children. Tasters preferred the colour, texture and taste of dishes prepared with the local variety, whether or not the grains were decorticated. Hedonic and preference tests showed no significant difference between the two biofortified varieties, but the cooks reported different behaviours during processing. Biofortified millet contained up to two times more iron than the local variety, reaching 6.5mg iron/100g dry matter. Iron and zinc contents remained higher in biofortified varieties even after decortication. Iron content in the dishes was highly variable, depending on iron loss and potential contamination during processing. The phytate-to-mineral molar ratios of all dishes indicated low iron absorption, independent of the millet variety, but improved zinc absorption in dishes prepared with biofortified varieties. The contribution of a dish prepared with one of the two biofortified millet varieties to the recommended iron and zinc intakes for 6-11-month-old children was estimated to be about 5% and 7%, respectively, compared to 2 and 4% for the same dish prepared with local millet. For 12-23-month-old children, the contribution to the recommended intakes was estimated to be about 14% and 12% with biofortified millet respectively, and about 6% and 7% with local millet. The use of biofortified millet varieties could be complementary to food diversification strategies to increase iron and zinc intakes. As in Ouagadougou, cereals are eaten in different forms by young children several times per day, iron and zinc intakes could be improved in the long term by using the biofortified varieties of pearl millet.